HOMICIDE IN ABBOTTABAD - Hassan, Qudsia; Shah, Mian Mujahid; Bashir, M. Zahid (Journal of Ayub Medical College Abbottabad, 2005)
Background: Homicide is one of the oldest crimes in human history. Although a large number of dimensions have been added to this crime, the age-old factors like revenge, rage, jealousy and honour persist even today. This study was conducted jointly at the attached hospitals of Women Medical College and Ayub Medical College, Abbottabad to know the various dimensions of the victims of homicide. Methods: The present study encompasses all 40 cases of homicide, which presented for autopsy at DHQ hospital and Ayub Medical Complex Abbottabad during the year 2002. The manner of death was categorized as homicide on the basis of police inquest and the autopsy findings. Results: The homicide rate in Abbottabad was found to be 4.22/100,000 per year. Males were the primary targets usually in their prime of youth with 40% victims between 20-29 years. Firearms formed the major weapon of offence. Most victims died before reaching the hospital. Deaths were more common during the daytime and in summer months. Conclusion: Homicide rate is on the lower side in Abbottabad amongst places where firearm possession is not strictly controlled, but can be further reduced. Limiting firearm possession alone can go a long way in this goal. Key Words: Homicide, age, daytime, Firearms, Abbottabad.